Code-Switching and Code-Mixing in Windah Basudara’s Roblox Gameplay - Artika Shitta Ramadani; Destia Puspitawati; Nur Hanifa Fitri Oktavianti; Teguh Sarosa (Talenta Publisher, 2026)
This study examines Windah Basudara's multilingual practices in his Roblox gaming livestream,